2006
DOI: 10.1017/s0022215106005512
|View full text |Cite
|
Sign up to set email alerts
|

A case of sensorineural deafness following ingestion of sildenafil

Abstract: We report a case of bilateral profound unremitting sensorineural hearing loss, in a 44-year-old male patient occurring after ingestion of sildenafil citrate 50 mg/day for 15 days. Audiological evaluation documented the findings. Sildenafil is an effective oral treatment for erectile dysfunction syndrome. It is being used and abused by many people as availability is easy and it can even be bought over the internet. Many patients are unaware of the harmful effects of sildenafil and take the drug without medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 7 publications
0
45
0
2
Order By: Relevance
“…However, a few studies to date have reported side effects of sildenafil that include flushing, headache, nasal congestion, heartburn, and non-arteritic anterior ischemic optic neuropathy. [3][4][5][6][7] Recently, sildenafil was reported to induce profound bilateral sensorineural hearing loss (SNHL) in a 44-year-old male patient following ingestion at 50 mg/d doses for 15 d. 8) SNHL is a type of hearing loss that involves the auditory nerve, inner ear, or central processing centers of the brain. SNHL can be evaluated as mild, moderate, or severe, and can cause complete deafness.…”
mentioning
confidence: 99%
“…However, a few studies to date have reported side effects of sildenafil that include flushing, headache, nasal congestion, heartburn, and non-arteritic anterior ischemic optic neuropathy. [3][4][5][6][7] Recently, sildenafil was reported to induce profound bilateral sensorineural hearing loss (SNHL) in a 44-year-old male patient following ingestion at 50 mg/d doses for 15 d. 8) SNHL is a type of hearing loss that involves the auditory nerve, inner ear, or central processing centers of the brain. SNHL can be evaluated as mild, moderate, or severe, and can cause complete deafness.…”
mentioning
confidence: 99%
“…Such interventions include independent patients and physicians' exposure to a new commercial media campaigns in Israel on MayJune 2007 with the aim of raising the awareness towards ED, and studies that were published during and around the study period regarding rare, severe side effects of PDE5-inh medications. 8,9 However, these processes most probably acted in both groups in both ways, and thus it is hard to assess their influence over theses variables. ED diagnosis and medical treatment correlate with the patients' age, so that younger patients had a greater chance to be diagnosed with ED and to be given prescriptions for PDE5-inh.…”
Section: Discussionmentioning
confidence: 99%
“…In the year 2007, an alarming report was published by Mukherjee and Shivakumar, in which a case of bilateral profound sensorineural hearing loss was described in 44-year-old man who took 50 mg/day of sildenafil for 2 weeks [23]. Based on that report, FDA issued a warning about possible sudden hearing loss among users of PDE5 inhibitors.…”
Section: Phosphodiesterase-5 (Pde5) Inhibitorsmentioning
confidence: 99%